The Catholic Meaning Behind The Name: Name Management Analysis - Sanga, Laurensius Dihe; Balun, Bernardus Somi (Tractare: Jurnal Ekonomi-Manajemen, 2024)
This writing aims to assert that not just anyone can use the name "Catholic" behind an institution. The name carries a myriad of meanings that must be considered wisely before being used. This research was conducted using a literature research method. Meanwhile, the data analysis technique used a descriptive analysis method. The researcher delved into the material based on topics from books, journals, and other literature studies. The results of this research indicate that the use of the name "Catholic" carries a burden of spirituality and morality that must be borne. In the context of teaching the faith, the relevant parties cannot spontaneously use the name "Catholic" but must consult and seek approval from the leaders. Therefore, certain institutions that use the name "Catholic" need to build effective management performance. The relevant parties must carefully consider and then use the name "Catholic" and be ready to take responsibility for it in their operational reality. Thus, the use of the name "Catholic" has philosophical, theological, and legal correlations.